(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study was carried out in the Laboratories of Al-Mussyab Technical college and in biology Department/Babylon university and Al-Jafflawy Avian farm in Babylon. During the period from October 2018 until March 2019 to investigate the effect water extracted of Melissa officinalis and Lead acetate in drinking water on semen physiological parameter and antioxidant status of Ross 308 Roosters. The study was held on 100 Roosters of Ross 308 at the age of 56-60 weeks with average weight 5-6 Kg. The Roosters were randomly distributed in equal groups. The First group(A) was given distilled water which regarded as control. The second group (B) was given the water extracted of Melissa officinalis leaves in the level of 100mg/Kg of body weight/L. The third group (C) was given Lead acetate in drinking water 0.5 mg/Kg of body weight/L. The Fourth group (D) which was given water extract of Melissa officinalis (100mg/Kg of B.W/L) and (0.5mg/Kg of B.W/L) of Lead acetate in drinking water. The semen was collected weekly to evaluate the ejaculated volume concentration, abnormalities, sperm resistance to salt and level of individual and mass mortality. The antioxidant status was evaluated by measuring malondialdehyde ( MDA) and total antioxidant capacity (TAC) also, body and testes weight was gain weekly. The study demonstrated that there was a significant increase in seminal ejaculate volume and concentration, salt-resistance and individual and mass mortality in the group(B) which given the water extracted of Melissa officinalis, and there was a significant increase in seminal abnormalities in the group(C) which given Lead acetate in drinking water. So the study demonstrated that there was a significant increase in TAC Level in seminal plasma of group(B) when there was a significant increase in Level of MDA in seminal plasma of group(C).